The Disproportionate Impact Of Dementia On Family And Unpaid Caregiving To Older Adults - Kasper, Judith D; Freedman, Vicki A; Spillman, Brenda C; Wolff, Jennifer L (Health affairs (Millwood, Va.), 2015)
The number of US adults ages sixty-five and older who are living with dementia is substantial and expected to grow, raising concerns about the demands that will be placed on family members and other unpaid caregivers. We used data from the 2011 National Health and Aging Trends Study and its companion study, the National Study of Caregiving, to investigate the role of dementia in caregiving. We found that among family and unpaid caregivers to older noninstitutionalized adults, one-third of caregivers, and 41 percent of the hours of help they provide, help people with dementia, who account for about 10 percent of older noninstitutionalized adults. Among older adults who receive help, the vast majority in both community and residential care settings other than nursing homes rely on family or unpaid caregivers (more than 90 percent and more than 80 percent, respectively), regardless of their dementia status. Caregiving is most intense, however, to older adults with dementia in community settings and from caregivers who are spouses or daughters or who live with the care recipient.